The Potential Of Traditional Knowledge As An Improvement Of The Welfare Of Communal Communities - Koto, Ismail (DE LEGA LATA: JURNAL ILMU HUKUM, 2024)
Intellectual property produced by indigenous or traditional communitiesstill not accommodated by regulations regarding Intellectual Property Rights.regarding the protection and recognition of communal intellectual property has beenof concern to society and international organizations. Right now it isThere are many claims made by other nations regarding the results of natural wealthas well as the cultural intellectual property of Indonesian society. Every ethnic group in Indonesia is believed to inherit communal intellectual property which is created based on human interaction with the natural environment in order to provide a way out of life's problems. This traditional knowledge is then manifested as a form of communal intellectual property in the perspective of the intellectual property rights legal regime. The government through the Ministry of Law and Human Rights, especially the Directorate General of Intellectual Property Rights, needs to immediately carry out intensive discussions on the Draft Law on the Protection of Traditional Knowledge and Traditional Culture Express. Efforts to overcome the challenges faced by the Government in providing intellectual property protection for traditional knowledge and traditional cultural expressions are carried out by the Government through the Ministry of Law and Human Rights, especially the Directorate General of Intellectual Property Rights, including, among other things, conducting open and continuous outreach and/or campaigns regarding knowledge understanding. traditional and traditional cultural expressions